CONTROL IN THE SYSTEM OF STRATEGIC MANAGEMENT EDUCATION BRANCH - BAZHENKOV, Ievgen (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considered controlling in the system of strategic management of the educational sector. The importance of applying progressive concepts of intra-industry management was analyzed. The concept of "Controlling" was defined as a cross-functional area of activity in the management system. The main opinions of world scientists regarding the definition of controlling were considered. The possibility of the process of implementing controlling in the system of strategic management of the educational sector was determined. The criteria on which the classic classification of controlling in the economic environment is based were listed. The classification orientation of controlling in the system of strategic management of the educational sector was illustrated. It was analyzed what strategic, tactical, operational, situational and local controlling are aimed at. Controllings were listed depending on the areas of implementation. The types of controlling were distinguished on the basis of equality. The types of controlling by scope of application were considered. The main points on which the introduction of controlling into the system of strategic management of the educational sector should be focused were determined. Proactive management in the field of education was analyzed, what it means, what is focused on. The main objectives of controlling in the system of strategic management of the educational sector were listed. The basic task of controlling in the system of strategic management of the educational sector was determined. The task of controlling in the system of strategic management of the educational sector was illustrated. The general functions of controlling in the system of strategic management of the educational sector were analyzed. These functions are the information function, communication function, management function, planning function, accounting and control function, and analytical function. The principles of the application of controlling were highlighted, which should be focused on when introducing the philosophy of controlling into the system of strategic management of the educational sector. Conclusions were made regarding controlling in the system of strategic management of the educational sector.